2016
DOI: 10.1590/s0100-736x2016000800002
|View full text |Cite
|
Sign up to set email alerts
|

Alterações bioquímicas, anatômicas e histopatológicas em fígado de Gallus gallus Linnaeus, 1758 experimentalmente infectados por Borrelia anserina Sakharoff, 1891

Abstract: Resumo: A espiroquetose aviária é uma enfermidade septicêmica de curso agudo, cosmopolita, que acomete diversas espécies aviárias, causada por Borrelia anserina e transmitida pelo carrapato Argas miniatus. O experimento teve como objetivos avaliar as alterações bioquímicas e anátomo-histopatológicas no fígado de Gallus gallus, causadas pela infecção experimental por B. anserina. Quarenta aves da espécie G. gallus foram divididas em quatro grupos inteiramente casualizados com 10 animais cada: G1 - inoculado com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The animals were divided into four groups: Group 1 (G1), 10 animals inoculated IM with blood serum (250μL) containing 3.7x10 6 spirochetes per microliter (inoculum with two previous blood passages in healthy poultry after being thawed from cryopreservation); Group 2 (G2), 10 animals inoculated IM with 250μL of saline 0.9% NaCl (control group "Serum"); Group 3 (G3), 10 animals infested with four Argas miniatus nymphs (3 rd instar) infected with B. anserina strain PL (Ataliba et al, 2007); Group 4 (G4), 10 animals infested with four A. miniatus nymphs (3 rd instar) free of infection by B. anserina (control group "Tick"). The protocols of the ticks and serum positives acquired were described in (Cepeda et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals were divided into four groups: Group 1 (G1), 10 animals inoculated IM with blood serum (250μL) containing 3.7x10 6 spirochetes per microliter (inoculum with two previous blood passages in healthy poultry after being thawed from cryopreservation); Group 2 (G2), 10 animals inoculated IM with 250μL of saline 0.9% NaCl (control group "Serum"); Group 3 (G3), 10 animals infested with four Argas miniatus nymphs (3 rd instar) infected with B. anserina strain PL (Ataliba et al, 2007); Group 4 (G4), 10 animals infested with four A. miniatus nymphs (3 rd instar) free of infection by B. anserina (control group "Tick"). The protocols of the ticks and serum positives acquired were described in (Cepeda et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the occurrence of anemia in poultry infected with B. anserina (El Nasri et al, 2010;Lisbôa et al, 2008) a hematological change that occurred in parallel with the spirochetemia period, which may evolve to self-healing in some cases (Lisbôa et al, 2008). Common necropsy findings include hepatomegaly with whitish spots and splenomegaly (Boero, 1967;Cepeda et al, 2016). The objective of the present study was to establish the infection dynamics of B. anserina in experimentally infected Gallus gallus to correlate its impact on the health and weight gain of the animals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…moderate hepatomegaly, congestion, irregular surface, red to cyanotic appearance) and different histopathological abnormalities (i.e. mononuclear inflammatory infiltrates, fibrinoid necrotic foci, dilatation of sinusoids and vacuolation of hepatocytes) [ 153 ].…”
Section: Historical Overview Of Rfgb In Latin Americamentioning
confidence: 99%